Komunikasi bisnis dan kinerja pt adi banuwa dalam peningkatan target perusahaan - Yunda, Cahya Kharisma; Jusnita, Raden Ayu Erni (Soetomo Communication and Humanities, 2020)
This research was conducted with the aim to find out PT Adi Banuwa's Business Communication Strategy in Improving Company Targets. The data source in this study uses the main informants and supporting informants. The main information is the directors of PT Adi Banuwa, while the supporting informants are from the employees of PT Adi Banuwa. Data collection uses interviews, observation and documentation. Analysis of the data used is a qualitative analysis method with data in the form of a graph of PT Adi Banuwa's target companies from 2017 to 2019. The theory used in this study is based on the Instrumental Model Of Persuation theory from Hovland. Based on the graph, it can be seen that from 2017 to 2019 there was an increase. Based on the results of the analysis conducted, PT Adi Banuwa should be able to add more business communication strategies so that the objectives of the company can be achieved more optimally.Keywords: communication; business; company target.